151k views
5 votes
Solve the exponential equation for x
3^7x+4=(1/27)^x-3

User Pan Ziyue
by
4.7k points

1 Answer

2 votes

Answer:

The solution is
x = (1)/(2)

Explanation:

To solve this exponential equation, we must write both sides as powers of 3.

The equation given is:


3^(7x + 4) = ((1)/(27))^(x-3)

Since
3^3 = 27, we have that
3^(-3) = (1)/(3^3) = (1)/(27), so
(1)/(27) = 3^(-3)

Then


3^(7x + 4) = ((1)/(27))^(x-3)


3^(7x + 4) = (3^(-3))^(x-3)


3^(7x + 4) = 3^(-3(x-3))


3^(7x + 4) = 3^(-3x + 9)

Since both sides are now powers of 3, we can equal them:


7x + 4 = -3x + 9


10x = 5


x = (5)/(10)


x = (1)/(2)

The solution is
x = (1)/(2)

User Paul Young
by
5.7k points